Strategies to accelerate skill learning - Havriluk, R. (Swimming World Magazine, 2020)
There are many different skill-learning approaches that can help a competitive swimmer improve his/her technique. For example, competitive swimming strokes "can be taught in their entirety or broken down into parts." While both the "whole" and "part" approaches can help swimmers progress in all four strokes, selecting the most appropriate method can accelerate skill learning.